(Re)Animating Stanislavsky: realizing aliveness in the virtual actor. Issue 1 (2nd January 2020) - Weinbren, Jon
ABSTRACT: This paper describes my initial attempts to create a believable Virtual Actor: an autonomous computer graphic character depiction that can convincingly portray actions and emotions in-the-moment, in real-time response to given circumstances of a dramatic context. The focus here is on the journey so far; and on some of the discoveries and realizations that have emerged from research and creative processes which have been brought into play. Konstantin Stanislavsky soon emerges in this process as a critical point of reference and inspiration – not only because of his own lifelong quest for means and methods to create 'life in art', but also as a compelling subject upon which to base the virtual actor's likeness. We are thus placed in a dialogue with Stanislavsky's legacy, and I am able to extend his notion of life in art on the stage to a more generalized 'beyond life' concept of aliveness . This is useful as it applies to character portrayal both in theatre and in in mediated forms such as animation, film and autonomously driven real-time computer graphic imagery. Along the way we also encounter historic and contemporary approaches to emotion, animation practice, and Artificial Intelligence in the form of Machine Learning. Graphical Abstract: